The Antecedents and Outcomes of Job Stress Experienced by School Administrators and Strategies for Coping with Stress - Serkan YUKSEL; Mustafa OZGENEL (Anı Publishing, 2022)
This study aims to determine the antecedents, consequences, and coping strategies of job stress among school administrators. A exploratory sequential design was used in the study. Interviews were conducted with 19 administrators using a semi-structured interview form to collect qualitative data. Quantitative data was collected using the Marmara Job Stress Scale. The scale was applied to 439 school administrators, and a t-test was used to determine if there were significant differences in the antecedents, consequences, and coping strategies of job stress. As a result of the qualitative interviews, it was found that the antecedents that cause most stress among school administrators are "responsibility" and "difficulty with colleagues, loneliness". As a result of the qualitative interviews, it was found that as a result of job stress, the administrators "do not have time for their families" and "are offensive to the business environment". According to qualitative data, school administrators were found to use individual coping strategies to manage job stress. The qualitative and quantitative results were interpreted together at the end of the study. As a result of the research, it is suggested that educational environments and legislation should be regulated according to the antecedents of work stress, which have a high effect on school administrators.